Were differences in tactical efficacy between the winners and losers teams and the final classification in the 2003 water polo world championship? - Argudo, F. M.; Ruiz, E.; Alonso, J. I. (Journal of Human Sport & Exercise, 2009)
This study has pursued to find the efficacy values in the playing micro-situations with or without ball possession present in Water polo and to analyze the relation between these and the condition of winner or loser, among winning teams, among losing teams and for the position that dealt in the final classification of the X World Championship. Were recorded in video all the female and male matches of the X Water polo World Championship, out agreed by consensus between two trained specialists, continuing the directors of the observational methodology. A specific software was designed for the analysis of the images and the management of the information. Has evaluated by means of coefficients the playing micro-situations in numerical equality, counterattack, defensive adjustment, simple temporary numerical inequality and penalty; obtaining efficacy values. For the statistically data analysis was carried out an ANOVA of a single factor followed by the Tukey test, taking as reference a value of p=.05. To conclude with, say that significant differences have been revealed in thirty six efficacy values in female category and forty six in male between winning and losing teams, eight between winning teams, the same ones between losing teams and seventeen between the positions that dealt in the final classification on having finished the above mentioned championship.